2023
DOI: 10.3390/polym15071716
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage and Marginal Integrity of Ormocer/Methacrylate-Based Bulk-Fill Resin Restorations in MOD Cavities: SEM and Stereomicroscopic Evaluation

Abstract: This in vitro study aimed to compare the microleakage and marginal integrity of methacrylate/ormocer-based bulk-fill composite (BFC) restorations used in cervical marginal relocation with two different layering thicknesses in mesio-occlusal-distal (MOD) cavities exposed to thermo-mechanical loading. Standard MOD cavities were prepared in 60 mandibular molars and assigned into three groups: x-tra fil/AF + x-tra base/XB, Tetric N-Ceram Bulk Fill/TNB + Tetric N-Flow Bulk Fill/TFB, and Admira Fusion x-tra/AFX + Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Since the literature abounds with comparative studies that have analyzed the efficiency of these methods in terms of marginal closure at the gingival threshold, but the performance of these techniques has not been analyzed in terms of mechanical strength [86][87][88][89].…”
Section: Discussionmentioning
confidence: 99%
“…Since the literature abounds with comparative studies that have analyzed the efficiency of these methods in terms of marginal closure at the gingival threshold, but the performance of these techniques has not been analyzed in terms of mechanical strength [86][87][88][89].…”
Section: Discussionmentioning
confidence: 99%
“…Ismail et al evaluated under scanning electron microscopy and digital microscopy that regardless of the technique used, microleakage of the deep margin elevation was not affected over time [30]. Meanwhile, Senol et al concluded that microleakage would be maintained if it is performed above the amelocemental junction [31].…”
Section: Marginal Adaptationmentioning
confidence: 99%
“…However, their impact on dental resin composite restorations has not been adequately explored. Furthermore, dental resin composite materials are usually the favored option for restorations, and numerous studies have investigated these materials’ properties [ 4 , 5 ]. Although restorative materials are less susceptible to erosion than enamel, their clinical performance is also affected by erosion.…”
Section: Introductionmentioning
confidence: 99%